Prevalence of chronic postsurgical hypoparathyroidism not adequately controlled: an analysis of a nationwide cohort of 337 patients - Díez, Juan J.; Anda, Emma; Pérez-Corral, Begoña; Paja, Miguel; Alcazar, Victoria; Sánchez-Ragnarsson, Cecilia; Orois, Aida; Romero-Lluch, Ana R.; Sambo, Marcel; Oleaga, Amelia; Caballero, Águeda; Alhambra, María R.; et al. (Frontiers in Endocrinology, 2024)
Purpose. The identification of patients with chronic hypoparathyroidism who are adequately (AC) or not adequately controlled (NAC) has clinical interest, since poor disease control is related to complications and mortality. We aimed to assess the prevalence of NAC patients in a cohort of subjects with postsurgical hypoparathyroidism.Methods. We performed a multicenter, retrospective, cohort study including patients from 16 Spanish hospitals with chronic hypoparathyroidism lasting ≥3 years. We analyzed disease control including biochemical profile and clinical wellness. For biochemical assessment we considered three criteria: criterion 1, normal serum calcium, phosphorus and calcium x phosphorus product; criterion 2, the above plus estimated glomerular filtration rate ≥60 ml/min/1.73 m 2 ; and criterion 3, the above plus normal 24hour urinary calcium excretion. A patient was considered AC if he or she met the biochemical criteria and was clinically well.Results. We included 337 patients with postsurgical hypoparathyroidism (84.3% women, median age 45[36-56] years, median time of follow-up 8.9[6.0-13.0] years). The proportions of NAC patients with criteria 1, 2 and 3 were, respectively, 45.9%, 49.2% and 63.1%. Patients who had dyslipidemia at the time of diagnosis presented a significantly higher risk of NAC disease (criterion 3;]; P=0.016).NAC patients (criterion 2) had a higher proportion of subjects with incident chronic kidney disease and eye disorders, and NAC patients (criterion 3) had a higher proportion of incident chronic kidney disease, nephrolithiasis and dyslipidemia than AC patients.The present study shows a strikingly high prevalence of NAC patients in the clinical practice of Spanish endocrinologists. Results suggest that NAC disease might be associated with some prevalent and incident comorbidities.